Canadian Agility Movement Skill Assessment (CAMSA) in a Spanish Context: Evidences of Reliability and Validity - Menescardi, Cristina; Villarrasa-Sapiña, Israel; Lander, Natalie; Estevan, Isaac (Measurement in Physical Education and Exercise Science, 2022)
The Canadian Agility and Movement Skill Assessment (CAMSA) is a circuit-based measure of motor competence. This study aimed to investigate the validity and reliability of CAMSA in Spanish children. A sample of 749 children participated voluntarily. Acceptable-to-good internal consistency (α =.54 and G-coefficient =.88) and moderate-to-excellent inter- (ICC:.83 to 1.00), intra-rater (ICC:.99 to 1.00) and test–retest reliability (ICC:.70 to.83) was found in convenience subsamples (n = 84 observers’ reliability; n = 69 test-retest). Concurrent validity was moderate (CAMSA score with Körperkoordinationstest für Kinder: r =.45; n = 90). Confirmatory factor analysis supported the one-factor model (CFI =.95; RMSEA =.02; SRMR =.02). Boys had higher scores than girls and older-children had higher scores than younger-children. The CAMSA can be used as a valid and reliable instrument for assessing motor competence in Spanish children.
Keywords: assessment; Confirmatory analysis; fundamental motor skills; motor competence; physical education; Scopus; JCR